2012
DOI: 10.1016/j.ajog.2012.06.066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic hypertension and pregestational diabetes on pregnancy outcomes

Abstract: OBJECTIVE The objective of the study was to examine the impact of chronic hypertension and pregestational diabetes on pregnancy outcomes. STUDY DESIGN This was a retrospective cohort study of 532,088 women undergoing singleton births in California in 2006. Women were categorized into chronic hypertension, pregestational diabetes, both, or neither. Pregnancy outcomes were compared using the χ2 test and multivariable logistic regression to control for potential confounders. RESULTS We identified differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 9 publications
1
54
1
1
Order By: Relevance
“…were more likely to meet WHO or Jamaica's ANC recommendations in this study. This is important to note because women with diabetes or hypertension are at particularly high risk for pregnancy and birth complications, such as preeclampsia, placental abruption and premature delivery [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…were more likely to meet WHO or Jamaica's ANC recommendations in this study. This is important to note because women with diabetes or hypertension are at particularly high risk for pregnancy and birth complications, such as preeclampsia, placental abruption and premature delivery [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It has also been shown that chronic hypertension in pregnancy has impacts on not only the rates of pregnancy-related hypertensive diagnoses (eg, preeclampsia/eclampsia, hemolysis, elevated liver enzymes, and low platelet count [HELLP]) but also fetal/neonatal outcomes, such as intrauterine fetal demise, stillbirth, and preterm birth. 10,[13][14][15][16][17][18] The association of chronic hypertension with preterm birth, both medically indicated and spontaneous, has been reported in multiple studies. 8,11,[15][16][17][18][19] The role of endothelial dysfunction and abnormal placentation has been posited in the literature as a mechanism for spontaneous preterm birth as well as intrauterine fetal growth restriction and small-for-gestational-age neonates.…”
mentioning
confidence: 99%
“…10,[13][14][15][16][17][18] The association of chronic hypertension with preterm birth, both medically indicated and spontaneous, has been reported in multiple studies. 8,11,[15][16][17][18][19] The role of endothelial dysfunction and abnormal placentation has been posited in the literature as a mechanism for spontaneous preterm birth as well as intrauterine fetal growth restriction and small-for-gestational-age neonates. 17 Data also suggest that different maternal racial/ethnic backgrounds confer a different degree of risk for chronic hypertension, although many of these data are confounded by multiple socioeconomic factors, such as diet, living conditions, and access to medical care.…”
mentioning
confidence: 99%
“…2 Pregnant women with T1DM are at increased risk of adverse pregnancy outcomes, including pre-eclampsia, preterm delivery, fetal growth restriction, perinatal death and neonatal morbidities related to diabetes mellitus. 1,2 The reported incidence of pre-eclampsia in this population is 10-40%. 2,3 Risk factors for the development of pre-eclampsia in women with diabetes mellitus include a long duration of diabetes mellitus, chronic hypertension, prior history of pre-eclampsia, presence of microalbuminuria or macroalbuminuria, nulliparity, high BMI and poor glycaemic control before 20 weeks of gestation.…”
Section: Baha M Sibaimentioning
confidence: 96%
“…The reported incidence ranges from 0.8% to 1.3% of all pregnancies. 1 Women with pre-gestational diabetes mellitus have either type 1 diabetes mellitus (T1DM) or type 2 diabetes mellitus. T1DM complicates 0.2-0.5% of all pregnancies.…”
Section: Baha M Sibaimentioning
confidence: 99%